Digital da’wah on religious moderation for Madurese women merchants in Tapal Kuda, Indonesia - Ilaihi, Wahyu; Zuhriyah, Luluk Fikri; Yusuf, M. (Jurnal Ilmu Dakwah, 2024)
Purpose - The purpose of this study was to examine the extent of da’wah by analyzing the assets of understanding, strategies for developing knowledge, and the results of understanding digital literacy in moderating religion among Madurese ethnic women in the Tapal Kuda area. Method - The study used the Asset-Based Community Development (ABCD) method, focusing on Pasar Induk (the main market) in Situbondo, which represents a hub of daily activities where Madurese women dominate as traders. Data collection involved participatory observation and mentoring, with a focus on identifying various types of assets. Result - The results showed that Madurese women possess several assets, namely physical assets, human assets, and social and institutional assets. The mentoring process revealed an increase in awareness among the women about utilizing these assets for digital literacy to better understand religious moderation in their daily lives. Implication –The method suggests improving digital literacy skills and awareness among marginalized groups to promote religious moderation and empower their economic activities. Originality/Value - This research is the first study to explore the integration of digital literacy and da’wah for religious moderation specifically among Madurese women merchants in a market setting, using the ABCD method as an intervention framework.*** Tujuan - Tujuan dari penelitian ini adalah untuk melihat sejauh mana dakwah dengan menganalisis aset pemahaman, strategi pengembangan pengetahuan, dan hasil pemahaman literasi digital dalam memoderasi agama di kalangan perempuan etnis Madura di wilayah Tapal Kuda. Metode - Penelitian ini menggunakan metode Pengembangan Masyarakat Berbasis Aset (ABCD), dengan fokus pada Pasar Induk di Situbondo, yang merupakan pusat kegiatan sehari-hari di mana perempuan Madura mendominasi sebagai pedagang. Pengumpulan data dilakukan melalui observasi partisipatif dan pendampingan, dengan fokus pada identifikasi berbagai jenis aset. Hasil - Hasil penelitian menunjukkan bahwa perempuan Madura memiliki beberapa aset, yaitu aset fisik, aset manusia, dan aset sosial dan kelembagaan. Proses pendampingan menunjukkan adanya peningkatan kesadaran di antara para perempuan untuk memanfaatkan aset-aset tersebut untuk literasi digital agar lebih memahami moderasi beragama dalam kehidupan sehari-hari. Implikasi - Metode ini menunjukkan peningkatan keterampilan literasi digital dan kesadaran di antara kelompok-kelompok yang terpinggirkan untuk mempromosikan moderasi beragama dan memberdayakan kegiatan ekonomi mereka. Keaslian/Nilai - Penelitian ini adalah studi pertama yang mengeksplorasi integrasi literasi digital dan dakwah untuk moderasi beragama secara khusus di kalangan pedagang perempuan Madura di lingkungan pasar, menggunakan metode ABCD sebagai kerangka kerja intervensi.